Ответ:
х = 7
Пошаговое объяснение:
х² - 10 * (х - 4) - 4х + 9 = 0
х² - 10х + 40 - 4х + 9 = 0
х² -14х + 49 = 0
D = b² - 4ac = (-14)² - 4 * 1 * 49 = 196 - 196 = 0
х = =
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
х = 7
Пошаговое объяснение:
х² - 10 * (х - 4) - 4х + 9 = 0
х² - 10х + 40 - 4х + 9 = 0
х² -14х + 49 = 0
D = b² - 4ac = (-14)² - 4 * 1 * 49 = 196 - 196 = 0
х =
= ![-\frac{-14}{2 *1} = \frac{14}{2}=7 -\frac{-14}{2 *1} = \frac{14}{2}=7](https://tex.z-dn.net/?f=-%5Cfrac%7B-14%7D%7B2%20%2A1%7D%20%3D%20%5Cfrac%7B14%7D%7B2%7D%3D7)